Concentration of luteinizing hormone in the serum of normal women - Garmendia Lorena, Fausto (2015)
We have determined the concentration of luteinizing hormone (LH) in the blood serum of 20 women of reproductive age, with normal menstrual cycles, without any hormonal treatment, only 6 had implemented a D. l. U. With this purpose, a radioimmunoassay technique was employed. In three cycles failed to show a significant increase in LH in the middle of it. In the 17 cycles, considered biphasic, ovulatory, a higher concentration of LH in the follicular phase was found (8 93 mU / ml, expressed in units of the 2nd. IRP-HMG) in the luteal phase (7.43 mU / ml) , p = 0.025. For an average duration of 30 days, the ovulatory LH surge was presented around the 17th day of the cycle, with wide variations between the 11th and the 25th day. The luteal phase lasted on average 14 days. The average concentration of LH peak was mesocíclico 79.97 mU / ml, which represented an increase of nine times higher LH concentration found during the follicular phase.